Significance of Interfacial Nanolayer and Mixed Convection in Radiative Casson Hybrid Nanofluid Flow by Permeable Rotating Cone - Batool, Kiran; Haq, Fazal; Fatima, Faria; Ali, Kashif (BioNanoScience, 2023)
Hybrid nanofluids exhibit higher thermal performance than conventional nanofluids. Due to improved thermal features of hybrid nanomaterials, these materials can be utilized in industrial and engineering devices to enhance their efficiency. Owing such applications, the aim objective of current study is to examine the behavior of radiative non-Newtonian Casson fluid submerged tiny particles of cobalt ferrite ( CoFe 2 O 4) and manganese zinc spinal ferrite ( Mn − Zn Fe 2 O 4). Behavior of flow is examined in a rotating porous cone with cluster interfacial layer impacts. Slip mechanisms of solid nanoparticles at the boundary of the surface are accounted. The governing flow model is acquired taking the effects of Darcy-Forchheimer, mixed convection, thermal radiation, and dissipation. The coupled PDEs representing flow are obtained by boundary layer suppositions. Transformation procedure is adopted to alter the PDEs into ODEs. The ODEs are changed into nonlinear system of algebraic equations through implicit finite difference methodology. The algebraic system is solved numerically using the successive over relaxation approach (SOR) in MATLAB software. The effective consequence of sundry variables on velocities (tangential & azimuthal), thermal field, Nusselt quantity, and skin friction coefficient are examined through tables and graphs. It is perceived from obtained results that higher interfacial nanolayer parameter improves the thermal field. Magnitude of heat transfer rate boosts via greater fluid material and thermal radiation values while it diminished through Eckert number and Prandtl number.